Association between meeting 24-h movement guidelines and health in children and adolescents aged 5–17 years: a systematic review and meta-analysis - Zhao, HanHua; Wu, Na; Haapala, Eero A.; Gao, Ying (Frontiers in Public Health, 2024)
Twenty-four-hour movement behaviors have significant implications for physical and mental health throughout one’s lifespan. Consistent with movement behaviors, several countries have formulated and published 24-h movement guidelines. This review summarized the studies related to 24-h movement guidelines among children and adolescents from six databases (MEDLINE, EMBASE, PubMed, Web of Science, CINAHL, and SPORTDiscus). In a total of 61 studies that discussed compliance with 24-h movement guidelines, the overall adherence rate was very low (7.6%), with boys exceeding girls, children surpassing adolescents, and regional differences. A total of 39 studies examined the associations between 24-h movement guidelines and health indicators. Findings indicated that meeting all three guidelines was favorably associated with adiposity, cardiometabolic health, mental and social health, physical fitness, health-related quality of life, academic achievement, cognitive development, perceived health, dietary patterns, and myopia. Future research should utilize longitudinal and experimental designs to enhance our understanding of the associations between 24-h movement guidelines and health indicators, thereby aiding the formulation and refinement of such guidelines. Systematic review registration https://www.crd.york.ac.uk/prospero/, CRD42023481230.